Green Tourism as a Form of Sustainable Tourism: Case Study of Nature Tourism Activities at Curug Cilember Bogor - Roels, Ni Made Sri Puspa Dewi; Sari, Wiwik Nirmala; Prawiro, Johann Wahyu Hasmoro (Media Wisata, 2025)
Curug Cilember is one of the destinations that carries the concept of nature tourism. Nature tourism is a form of green tourism, which is an environmentally friendly tourism activity. The tourist attractions owned by Curug Cilember are the uniqueness of seven waterfalls in one area and a butterfly conservation park. The purpose of this study is to identify the natural tourist attractions in the Curug Cilember. The research method used is qualitative research with an exploratory approach. Data collection methods through observation, interviews, and documentation. Determination of informants with purposive sampling, which involved five informants from the manager. The results of this study show that Curug Cilember has implemented green tourism with sustainable management. The area is managed by the Jogjogan Village community by maintaining the ecosystem. Socio-cultural sustainability by maintaining myths that are believed, and environmental sustainability by implementing conservation of the sustainability of flora and fauna diversity. The category of nature tourism activities in the Curug Cilember Forest Tourism Area has met five aspects, starting from the information aspect, the diversity aspect, beauty and uniqueness, the adventure of living animals and cross-nature adventures. Natural tourism activities such as natural conditions, topography and ecology, as well as the uniqueness of flora and fauna, support Curug Cilember as a green image destination.